INTERPRETATION OF ALLOMETRIC GROWTH PATTERNS OF FISH SPECIES FROM DADIN-KOWA RESERVOIR - S., NAZEEF; R., YERIMA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
The study examined and interpreted the allometric growth patterns of fish species of Dadin-Kowa Reservoir employing “Regression” function. A total of 25 fish species were examined for their Length Weight Relationships (LWR). Of which seventeen fish species had negative allometric growth with major scourge on Pollimyrus isidori (b-index = 1.94), while Brycinus nurse conformed to the peak LWR positive allometric growth (b-index = 3.46). The vast distribution of the landed fish species indicated signs of overfishing. These signs may lead to growth and recruitment overfishing in the possible future. If managed properly; the reservoir can yield fish species with good table size and sustainable economy.